2018
DOI: 10.3390/fermentation4040091
|View full text |Cite
|
Sign up to set email alerts
|

Beer–The Importance of Colloidal Stability (Non-Biological Haze)

Abstract: Today’s beer differs in many ways from the original hazy brew made from grains and water left in the sun to ferment. The development of brewing procedures introduced filtration and colloidal stabilization as key elements in beer preservation and stability. Colloidal stability of beer is the most important factor in beer quality. Colloidal particles significantly shorten beer’s storage time, but most importantly, also influence its appearance. Colloidal stabilization involves one or more procedures that are app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
0
32
0
2
Order By: Relevance
“…The average pH of all the samples was 3.1 ± 0.31 which is in agreement with studies reported by Mapitse et al [7] who reported an average pH of 3.1 ± 0.15. pH influences the overall physiological characteristics of alcoholic beverages, such as taste, color and microbiological stability. Most importantly, pH also strongly influences sanitation of the product, an attribute important for increasing shelf life of the brew [75]. Other than the presence of ethanol, the acidic pH is likely the other reason why there were no bacteria isolated from khadi.…”
Section: The Ph Of Khadi An Important Factor In Preservation Of the mentioning
confidence: 99%
“…The average pH of all the samples was 3.1 ± 0.31 which is in agreement with studies reported by Mapitse et al [7] who reported an average pH of 3.1 ± 0.15. pH influences the overall physiological characteristics of alcoholic beverages, such as taste, color and microbiological stability. Most importantly, pH also strongly influences sanitation of the product, an attribute important for increasing shelf life of the brew [75]. Other than the presence of ethanol, the acidic pH is likely the other reason why there were no bacteria isolated from khadi.…”
Section: The Ph Of Khadi An Important Factor In Preservation Of the mentioning
confidence: 99%
“…In our previous works, we proposed nanocomposites based on CS and nanoclays in very low concentrations (1–5% w / w ) [ 12 ] and systems based on CS and nanoclays in high concentrations (70–80% w / w ) [ 14 ], maintaining, in both cases, the total weight of the composite constant. Papain from Carica papaya L. latex (EC 3.4.22.2), a cysteine protease applied in brewing for the removal of chill haze [ 18 ] and for the clarification treatment of pomegranate juice [ 19 ], has been covalently immobilized on CS. Moreover, Benucci et al [ 20 ] immobilized papain on commercial chitosan beads by direct linkage for the protein stabilization of white wines.…”
Section: Introductionmentioning
confidence: 99%
“…A beer perceived as flat showed little nucleation activity (bubbling) in the glass, regardless of its normal CO 2 content. Also, active bubbling regenerates the head [46][47][48].…”
Section: Bubble Size Distribution and Nucleation In Beermentioning
confidence: 99%